The Oxford handbook of Mary - Maunder, Chris ca. 20./21. Jh. (Oxford handbooks online Religion, 2019)
'The Oxford Handbook of Mary' offers an interdisciplinary guide to Marian Studies, including chapters on textual, literary, and media analysis; theology; Church history; art history; studies on devotion in a variety of forms; cultural history; folk tradition; gender analysis; apparitions and apocalypticism. Featuring contributions from a distinguished group of international scholars, the handbook looks at both Eastern and Western perspectives and attempts to correct imbalance in previous books on Mary towards the West. The volume also considers Mary in Islam and pilgrimages shared by Christian, Muslim, and Jewish adherents. While Mary can be a source of theological disagreement, this authoritative collection shows Mary's rich potential for inter-faith and inter-denominational dialogue and shared experience